Women in culture an intersectional anthology for gender and women's studies - Scott, Bonnie Kime 1944-; Cayleff, Susan E.; Donadey, Anne; Lara, Irene (Chichester, West Sussex, United Kingdom John Wiley & Sons, 2017)
"The thoroughly revised Women in Culture 2/e explores the intersections of gender, race, sexuality, gender identity, and spirituality from the perspectives of diverse global locations. Its strong humanities content, including illustrations and creative writing, uniquely embraces the creative aspects of the field" -- Provided by publisher.
1. Introduction to feminist concepts and issues -- 2. Stories of identity and community -- 3. Histories of feminism -- 4. Women and gender in arts and media -- 5. Sexualities and genders -- 6. Body politics -- 7. Reproductive and environmental justice -- 8. Violence and resistance -- 9. Healing and spirituality -- 10. Activism for the future -- Glossary -- Timeline -- Index.
Earlier edition: 1998
First edition titled "Women in culture : a women's studies anthology" edited by Lucinda Joy Peach.
Includes bibliographical references and index.
Keywords: Women; Women in popular culture; Sex role; Social values; Feminist criticism